Justice, Civilization, and the Death Penalty : Jeffrey H. Reiman. - Howder, Shelley; Zeman, Tamara M.; Zenda, Benjamin A.; Stygar, Danielle M.; Beauchaine, D. John (My University, 2009)
This study examines Jeffrey H. Reiman's arguements against capital punishment: 1) The death penalty is detrimental to civilization 2) The death penalty is no more effective as a deterrent to crime than life in prison 3) The death penalty teaches society that murder is sometimes acceptable 4) The death penalty is a form of torture, psychological and physical.
Jeffrey H. Reiman : Justice, Civilization, and the Death Penalty.
Color poster presenting arguments and rebuttals made by J. Beauchaine, J. Bresina, S. Howder, D. Stygar, T. Zeman, and B. Zenda.
Keywords: Capital punishment--Moral and ethical aspects; Criminal justice, Administration of--Philosophy; Posters; Punishment in crime deterrence; Civilization--Philosophy